Several Digital Literatures for Children - Girsang, Martina; Sihotang, Anisa; Pasaribu, Dona; Daeli, Norbetha; Laia, Reftalenta (International Journal of Education and Digital Learning (IJEDL), 2023)
Children's literature is literary writing aimed at early childhood where today children's literature has experienced many developments from time to time both in terms of form and writing. Children's literature experiences many developments over time both in various media, such as digital and non-digital. This article focuses on digital literary media. Digital literacy is the capability to utilize technology and information from digital devices successfully and efficiently in a variety of contexts, including education, employment, and daily life, especially in the field of children's literature, education, form and genre will continue to be considered, so that children who read get good information. The purpose of this article is to explore various digital media of children's literature. This research used qualitative research method through library research. Data collection in this study was carried out by exploring several journals, books and documents (both print and electronic) and other sources of data and/or information related to research. The result of the study indicate that there are several digital media literature, namely CD-Roms, video games and picture book apps that have advantages such as entertaining children, helping children's cognitive and emotional development, helps and develops the reasoning and potential of the child, developing children's imagination and creativity.